Metodologias de testes para avaliação do potencial fisiológico de sementes de mogango (Cucurbita pepo L.) - Härter, Letícia dos Santos Hölbig (2013)
The Mogango (Cucurbita pepo L.) belongs to the Cucurbitaceae family. Propagtion of the mogango is done by seeds that can be sown directly in the place of cultivation or in trays with individual cells for later transplantation, being necessary the use of seeds with high vigor. The final quality of a vegetable crop depends among other factors, in obtain a proper and uniform population of plants in the field. Vigor tests provide more sensitive indexes of physiological quality that germination test, so any event that precedes the loss of germination can serve as a basis for evaluating the vigor force. The aim of this study was to evaluate methodologies of controlled deterioration test and accelerated aging test, for vigor expression in seeds of mogango, and compare the most promising results of tests to assess the performance of vigor with in lots during storage. Seeds of mogango cultivar Sul Mineiro, represented by six lots of three different seed companies. The seeds were characterized for quality through testing moisture, germination, first count, cold test, shoot length, root length, seedling emergence, speed of emergence and root length in greenhouse ; accelerated aging tests were conducted using the following methodologies: traditional, brine - 40g NaCl.100mL-1 water and brine unsaturated - 11gNaCl.100mL-1 of water at 41 °C for periods of 24, 48, 72 and 96 hours. And the controlled deterioration test, adjusting the water content of seeds to 15%, 20% and 25% at 41 °C for 24, 48 and 72 hours. Assessments were performed every 60 days. The test was conducted in a completely randomized, the means were compared with the Tukey test at a probability level of 5% and compared by linear correlation. It was found that to stratify seed lots of mogango by vigor the traditional accelerating test methodology recommended was using an aging period of 24 hours and 41 ºC; and the vigor of seed lots of mogango by controlled deterioration test indicates the us of the initial water content of 15% and periods of stress for 24 hours at 41 °C.